2022
DOI: 10.3389/fimmu.2022.936707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune hub genes participating in the pathogenesis and progression of Vogt-Koyanagi-Harada disease

Abstract: BackgroundVogt-Koyanagi-Harada (VKH) disease is an autoimmune inflammatory disorder characterized by bilateral granulomatous uveitis. The objective of this study was to identify immune hub genes involved in the pathogenesis and progression of VKH disease.MethodsHigh throughput sequencing data were downloaded from the Gene Expression Omnibus (GEO) and an immune dataset was downloaded from ImmPort. Immune differentially expressed genes (DEGs) were obtained from their intersection in the GEO and ImmPort datasets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…KLRC3 is a member of the natural killer group (NKG) 2, which can specifically regulate humoral and cellular immunity. Although the role of KLRC3 in APS and RIF pathogenesis has not yet been investigated, it is associated with the development of other autoimmune diseases, metabolic diseases, and tumors (55)(56)(57). Downregulation of KLRC3 may lead to abnormal expression of the NKG2E receptor, which results in insufficient NK cell activation and defective NK cell function (56).…”
Section: Discussionmentioning
confidence: 99%
“…KLRC3 is a member of the natural killer group (NKG) 2, which can specifically regulate humoral and cellular immunity. Although the role of KLRC3 in APS and RIF pathogenesis has not yet been investigated, it is associated with the development of other autoimmune diseases, metabolic diseases, and tumors (55)(56)(57). Downregulation of KLRC3 may lead to abnormal expression of the NKG2E receptor, which results in insufficient NK cell activation and defective NK cell function (56).…”
Section: Discussionmentioning
confidence: 99%
“…Vogt–Koyanagi–Harada (VKH) disease is a rare bilateral granulomatous uveitis involving pigmented structures [ 1 ]. Although the precise etiology of VKH disease is still largely unknown, accumulating previous studies have suggested that genetic factors play an essential role in VKH disease development [ 2 , 3 ]. Familial occurrence of VKH disease is rare, while authors still provide some evidence to suggest that the condition may be inherited [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%